A systematic approach for developing a robust LC–MS/MS method for bioanalysis. (January 2013) - Meng, Min; Wang, Laixin; Voelker, Troy; Reuschel, Scott; Van Horne, KC; Bennett, Patrick
In order to meet the drug discovery and development needs of pharmaceutical companies, CROs are constantly challenged by the requirements for rapid LC–MS/MS method development prior to method validation and sample analysis. In order to meet this challenge, a comprehensive method development program, nicknamed 'Amoeba™', which uses a series of written protocols for standardized and efficient method development was developed. In this paper, the genesis of the Amoeba method development program is elucidated in detail and a number of case studies are presented to showcase the execution of the Amoeba method development program. Using this program, the majority of the most critical information regarding the assay can be captured. While the Amoeba program has been proven to be effective, we recognize that the development of a robust bioanalytical method for use in pharmaceutical industry also requires the careful consideration of many critical parameters and the ability to identify and resolve potential issues. The refinement of the assay relies on further evaluation of several critical factors including, but not limited to, internal standard response, matrix effects (phospholipid or nonphospholipid related) and carryover.